GEOLOGICAL AND GEOCHEMICAL FEATURES OF THE KOPAONIK INTRUSIVE COMPLEX (VARDAR ZONE, SERBIA) - Zelic, Mario; Agostini, Samuele; Marroni, Michele; Pandolfi, Luca; Tonarini, Sonia (Ofioliti, 2010)
In the Vardar Zone of the Dinaric-Hellenic Belt, several intrusive magmatic bodies with an age spanning from Early Cretaceous to Miocene occur. One of the main bodies is represented by the Kopaonik Intrusive Complex that crops out in Southern Serbia in an area of about 90 km2. This paper deals with the geological and geochemical features of the Kopaonik Intrusive Complex, in order to provide useful constraints for its interpretation in the frame of the post-collisional magmatic activity that characterized the more internal zone of the Dinaric-Hellenic Belt. The Kopaonik intrusive complex is characterized by a dome-like structure consisting of three concentric magmatic facies, including lithotypes ranging from qtz-diorites to granodiorites and qtz-monzonites, with a gradual and continuing transition between them. The collected data indicate that the Kopaonik granitoids are I-type, with high-K calc-alkaline affinity. The origin of the intrusive complex is partially obliterated by shallow interaction between the qtzdioritic rocks and carbonate host rocks, affecting Ca-Sr contents and 87Sr/86Sr ratios. Nevertheless, the collected geological, petrographical and petrochemical data suggest a strong genetic relationship of the three facies. A minimum emplacement age of 31.5±0.3 Ma (Early Oligocene) is provided by Rb-Sr wholerock biotite age. The Kopaonik intrusives belong to a continuous Late Paleogene-Middle Miocene magmatic belt developed throughout the Balkan Peninsula from the Eastern Alps to Northwestern Turkey, and linked with subduction of the NeoTethys oceanic plate under the Eurasia. In this framework, the source of the Kopaonik magmatic rocks can be identified in a mantle wedge strongly modified by subduction-induced metasomatism.